CURRENT ISSUES AND PROSPECTS FOR THE DEVELOPMENT OF SMALL BUSINESS IN THE REPUBLIC OF UZBEKISTAN (Innovations in Science and Technologies, 2025)
This article is devoted to current issues and future development opportunities in the field of small business in the Republic. During our research, we examined the work of the world's leading experts and researchers along with local scientists. A number of problems that impede the further development of small business were investigated, and a number of promising areas of small business in our country were also analyzed. In conclusion, the results were summed up and several proposals were put forward to improve the business environment in the Republic of Uzbekistan.